Accountability Analysis of Village Fun Management and Village Development to Allocation of Village Funds - Moh. Ali Wafa; Isnaini Anniswati Rosyida; Istifak Iyatus Sholikha (Basic and Applied Accounting Research Journal, 2023)
This study aims to determine and describe the Accountability of Village Fund Management and Village Development in the Allocation of Village Funds Mrutuk, Widang District, Tuban Regency which includes (1) Planning, (2) Implementation, (3) accountability. The method used in this study is a qualitative descriptive method. The technique used in collecting data through interviews and direct observation of the object. This research shows that at the planning, implementation, accountability, and development stages, the telash is in accordance with the applicable procedures and the management has been carried out in an accountable manner. The results of this study indicate that the management of Village Finance in general is that the management of Village Finance has achieved accountability. In addition, there is still a need for intensive village assistance from the local government in helping villages to realize village financial management accountability.